IDENTIFICATION OF THE TYPE OF GROUPER (Serranidae) RESULTS FROM THE CATCH OF LEWOLEBA FISHERMEN LANDED AT THE TPI LEWOLEBA MARKET - Lasmi, Lasmi; Halija, Siti (Universitas Mataram, 2025)
Grouper is an important economic commodity whose existence continues to be sought after by fishermen. Knowing the types of fish landed and marketed at TPI Lewoleba will be very helpful as a basis for sustainable fisheries management that is appropriate for improving the quality of fish on the market, starting from the fishing management process, handling fishery products, processing, marketing and so on, so that it can also improve the welfare of the fishing community. This research was carried out at TPI Lewoleba in September 2024 – December 2024. The aim of this research was to determine the type of grouper (Serranidae) caught by fishermen landed at the TPI Lewoleba market. The method used in this research is descriptive research method. The results of the research are the types of grouper fish (Serranidae) landed at the TPI Lewoleba market, namely the species Cephalopholis boenak, Variola louti, Epinephelus ongus, Epinephelus fasciatus, and Cephalopholis miniata, Plectropomus leopardus, Epinephelus coeruleopunctatus, and Anyperodon leucogrammicus, Plectropomus oligacanthus, Plectropomus areolatus, and Epinephelus macrospilos, Cephalopholis sonnerati and Epinephelus undulosus. Based on the identification results of grouper fish (Serranidae) landed at the Lewoleba Fish Auction Place (TPI), 13 species were recorded.